Serum Insulin-like Growth Factor I (IGF-I), IGF-Binding Proteins-1 and -3, and Postnatal Growth of Late Preterm Infants - Giapros, V. I.; Schiza, V.; Challa, A. S.; Pantou, C.; Theocharis, P. D.; Andronikou, S. K. (Hormone and Metabolic Research, 2012)
Late preterm infants may have impaired early growth. The role of circulating insulin-like growth factors (IGFs) in the regulation of postnatal growth of these infants is unclear. The aim of the study was to investigate prospectively the serum levels of IGFs during the first year of life in late preterm infants and their association with birth weight and early postnatal growth. The study was conducted on 112 infants, born appropriate for gestational age (GA) at GA 32–36 weeks. Serum levels of IGF-I and IGF-binding proteins (IGFBP) -1 and -3, and anthropometric measurements were recorded at the chronological age of 2 and 6 weeks, and 3, 6, 9, and 12 months. The mean levels of both IGF-I and IGFBP-3 were found to be lower at 2 and 6 weeks, 82±44, 100±31 ng/ml, and 1.7±0.8, 2.1±1 μg/ml, respectively, but then rose and remained stable between 3 and 12 months. The levels of IGFBP-1 were lower at the 3 first study points and increased gradually thereafter. Birth weight correlated positively with the level IGF-I at 2 and 6 weeks (R=0.35, 0.37; p<0.01), but negatively at 12 months (R= − 0.34; p<0.01), independent of other factors. At all study points up to 6 months, the level of IGF-I was higher in infants who showed more rapid growth in either body weight or crown heel length. In late preterm infants, the serum IGF-I level is closely related to early accelerated growth. Its diverse associations with birth weight may imply a regulatory effect on regression of growth towards the mean.
Keywords: IGF-I; IGFBP-3; IGFBP-1; accelerated growth; infant; late-preterm